Nutritional Rickets Due to Severe Food Selectivity in Autism Spectrum Disorder. Issue 1 (January 2021) - Hartman, Jacob S.; Silver, Alyssa H.
ABSTRACT: Objective: Studies have detected differences in various measures of bone health between individuals with autism spectrum disorder (ASD) and their peers. However, these measures do not amount to direct clinical evidence of increased orthopedic pathology in this population. Some of the most compelling evidence to this effect comes from case reports of nutritional rickets in children with ASD. We report on 1 such case that, to our knowledge, is the first report of nutritional rickets in ASD necessitating corrective surgery. Methods: Case report, review of relevant literature, and implications for further research. Results: An 11-year-old girl with ASD was admitted for postoperative medical comanagement after successful repair of bilateral genu valgum (knock knees). On admission, the patient's mother reported that the patient was a "picky eater." No cause had been determined preoperatively, although the deformity had developed at 10 years of age, thereby qualifying as pathologic. The medical team considered rickets because of the patient's limited diet. Subsequent laboratory work demonstrated hypocalcemia, vitamin D deficiency, and secondary hyperparathyroidism. The patient was diagnosed with nutritional rickets due to inadequate vitamin D intake, a consequence of severe food selectivity associated with ASD. Conclusion: This case exemplifies the extreme orthopedic and metabolic complications that can result from food selectivity in children with ASD, pointing to the need for further research into the prevalence and causes of orthopedic pathology and nutritional rickets in this population. The case also underscores the need for evidence-based guidelines to prevent orthopedic pathology in children with ASD.